Coupling of internal and external cooling of gas turbine blades. (22nd May 2014) - Ghezali, F.; Azzi, A.; Bouzidane, A.
<x content-type="archive" xml:space="preserve">Abstract</x> Showerhead cooling process which consists of internal convective cooling and external film cooling of a turbine blade is investigated using ANSYS-CFX software. The aim of the present investigation is to provide a better understanding of the fundamental nature of showerhead cooling using the three dimensional Reynolds averaged Navier Stokes analysis. A numerical model has been developed to study the effects of coupled internal and external cooling of the leading edge for a semi-elliptical body shape with the SST k-ω model. This model consists of all internal flow passages and cooling hole rows at the leading edge. The numerical results obtained are discussed and compared with experimental data available in the literature. The results show that the cooling efficiency increases with the increase of the blowing ratio and the Mach number, therefore, the overall efficiency for the steel becomes less important compared to the plexiglas which has a low thermal conductivity.